Tracing and accessing arabic periodicals : An overview - Suja’, Balqis; Zakaria, Maznah (Persatuan Pustakawan Malaysia, 2011)
Arabic periodicals are mostly published in the Arab countries and are usually untraceable from the international indexing and abstracting services. This article presents a brief descriptive overview of the characteristics of Arabic periodicals and explores the existing bibliographical control tools as found in the literature. The discussion encompasses issues on Arabic periodicals’ bibliographical access and physical access. The Internet was searched to identify available current contents lists, individual indexes, collective indexes (general and specific), institutional indexes, and bibliographic databases (general and specific). The final part of the article will include a review on the Malaysian Union List of Serials and Katalog Induk Kebangsaan (Malaysian Union Catalogue) on whether retrieval using the descriptor terms will yield local Arabic periodicals collection available in the database. The results showed the extent to which the available information on Arabic periodicals is helpful for local libraries facilitate Arabic periodicals reference.